A family of low molecular-weight, organic catalysts for reductive C–C bond formation1. Issue 73 (21st September 2015) - Shaaban, Saad; Jolit, Anaïs; Petkova, Desislava; Maulide, Nuno
<x xml:space="preserve">Abstract</x> Using only small amounts of a hydrazine catalyst, the coupling of diazonium salts to a variety of reactive partners has been achieved, without the requirement for either metal adjuvants or irradiation with visible or ultraviolet light.